Vertical Continuous Meniscal Suture Technique - Rocha de Faria, José Leonardo (Arthrosc Tech, 2020)
Meniscal injuries are common in the population, representing the major cause of functional impairment in the knee. Vertical longitudinal injuries of the meniscus can be stable or unstable. When extensive, they are commonly unstable and can lead to clinical signs of significant functional disability. Vertical longitudinal injuries have the best prognosis for repair, especially when occurring in the meniscal periphery, called the red-red zone. A recently developed type of meniscal suture device called Meniscus 4 A-II enables the surgeon to perform a meniscal suture from the inside-out continuously, reducing surgical time. Because it allows the surgeon to use a single and inexpensive device to repair the entire injury, costs are significantly reduced. Here, an approach to carry out continuous meniscal repair with vertical sutures is described. This technique warrants excellent stability to the meniscal repair, increasing the chances of a successful outcome. We believe that the popularization of the repair technique from the inside out using the Meniscus 4-All device will help many surgeons around the world save menisci that otherwise would have a great chance of being excised, since it is a cheap, reproducible, and easy-to-handle device.